2005
DOI: 10.1007/0-387-24199-x_5
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Metastasis of Primary Central Nervous System (CNS) Neoplasms

Abstract: Abstract:Leptomeningeal dissemination of primary CNS tumors varies widely by histologic subtype. In certain tumors including medulloblastoma, ependymoma, germ cell tumors, and primary CNS lymphoma, seeding of the cerebrospinal fluid space is a critical factor in determining stage, prognosis and appropriate therapy. Other tumor types, such as glioma, may have radiographic evidence of leptomeningeal metastases without clear impact on prognosis or therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 74 publications
0
15
0
1
Order By: Relevance
“…Altogether, our findings indicate that high MYC levels drive BMP7 overexpression, promoting cell survival in MB cells. This observation suggests the potential relevance ofIntroduction Medulloblastoma (MB) represents >20% of all pediatric tumors of the central nervous system (Gurney and Kadan-Lottick, 2001), and is characterized by aggressive clinical behavior and high risk of leptomeningeal dissemination (Engelhard and Corsten, 2005). Multimodal therapy (surgery, radiotherapy and chemotherapy) has improved the overall survival rate.…”
mentioning
confidence: 99%
“…Altogether, our findings indicate that high MYC levels drive BMP7 overexpression, promoting cell survival in MB cells. This observation suggests the potential relevance ofIntroduction Medulloblastoma (MB) represents >20% of all pediatric tumors of the central nervous system (Gurney and Kadan-Lottick, 2001), and is characterized by aggressive clinical behavior and high risk of leptomeningeal dissemination (Engelhard and Corsten, 2005). Multimodal therapy (surgery, radiotherapy and chemotherapy) has improved the overall survival rate.…”
mentioning
confidence: 99%
“…Thirty of 87 patients (34.5%) developed dissemination, which is higher than the 7–27% that has been reported elsewhere [10]. Patients with high-grade gliomas who received high-dose radiation therapy had a higher rate of CSFD than those who had received lower doses [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although CSF dissemination may be more common [7, 8, 9] than generally realized [10], it is unusual following current standard therapy for high-grade gliomas. Mandel et al [11] have reported that in a series of 595 GBM patients treated in clinical trials at the Baylor College of Medicine, 36 (4%) developed dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of leptomeningeal metastasis of primary central nervous system (CNS) tumors has been reported to range from 7% to 27%, but extra-CNS GCT metastasis is rare (Engelhard et al 2005). There has been only one report in the last 10 years (Miranda et al 2005).…”
Section: Discussionmentioning
confidence: 99%